Recondition injector nozzle and its pressure effect on performance parameters of diesel engine Komatsu types SAA12V140E-1 - Amiral Aziz; Zul Fahmi (Universitas Mercu Buana, 2022)
The injector is one of the main components of a diesel engine fuel system. A typical fuel injector has two basic parts: the nozzle and the injector body. If either of these components is clogged or damaged, it will compromise the entire performance of the engine. Any injector problem can easily be fixed by cleaning, reconditioning, or replacement. If the engine is producing low power, replacing the injector nozzle with a new injector nozzle is necessary, so that engine performance reaches standard performance. However, replacing a new injector nozzle carries a huge maintenance cost. In this research, reconditioning or repairing the used injector nozzle to increase the fuel injection pressure in the engine is one solution that can be done to improve engine performance with low maintenance costs. The testing results found that brake power and brake thermal efficiency increase as fuel injection pressure increases, but specific fuel consumption decreases. For both the used injector and repaired injector, the minimum specific fuel consumption (SFC) does occur at the maximum brake power (BP) not generated. This means that the diesel engine never occurs in a condition of maximum power generated with minimum specific fuel consumption or vice versa.